The development of didactical tetrahedron design on learning integers to improve algebraic thinking skills - Hajizah, Mimi Nur; Salsabila, Ellis; Hadi, Ibnu; Meganingtyas, Devi Eka Wardani (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to develop a didactical tetrahedron design for teaching integers by integrating the components of teacher, student, learning materials, and technology to enhance students’ algebraic thinking skills. The study adopts a Design-Based Research approach grounded in Realistic Mathematics Education (RME). The research was conducted in two phases involving the development of a hypothetical didactical tetrahedron design, which was later refined through classroom teaching experiments. Both qualitative and quantitative instruments are used. The statistical analysis of the questionnaires and the narrative analysis of the qualitative instruments have been triangulated. Based on the analysis of students’ difficulties, a conjectured didactical tetrahedron design was developed. Then the developed design was implemented in the teaching experiment. The implementation of the didactical tetrahedron design significantly improved students’ algebraic thinking abilities. Students in the experimental group showed higher N-Gain scores and better conceptual understanding than those in the control group. The didactical tetrahedron design is effective in addressing common difficulties students face when learning integers and promotes the development of algebraic thinking. This design provides educators with a structured and technology-integrated instructional model that supports meaningful learning and enhances students’ algebraic thinking skills.